Prevalence and Antimicrobial Resistance of Listeria monocytogenes Isolated from Dairy Products in Romania - Filippos Georgios Nikolaou; Liora Mihaela Colobatiu; Laurentiu Mihai Ciupescu; Alexandra Tabaran; Ariana Raluca Hategan; Romolica Mihaiu; Radu Tanasuica; Magdalena Maria Poenaru; Marian Mihaiu (Antibiotics)
Background/Objectives: Listeria monocytogenes is a significant foodborne pathogen associated with dairy products, which can pose serious public health risks, particularly for vulnerable populations. This study aimed to assess the prevalence, serotype distribution, and antimicrobial resistance profiles of Listeria monocytogenes isolated from dairy products collected in Romania over a three-year period (2021–2023). To the best of our knowledge, this is the first comprehensive study addressing these issues within the country. Methods: A total of 10,306 dairy samples, including milk, cheeses, ice cream, yogurt, and other dairy-based products, were collected and analyzed using standard microbiological methods. Molecular serotyping was performed to identify the most common serogroups. The antimicrobial susceptibility of the isolates was also conducted. Results: The overall prevalence of Listeria monocytogenes was 0.41% (43/10,306). The most frequently detected serogroup was IVb (74.41%), followed by IIa (23.25%) and IIb (2.32%). Ice cream was the most affected product, followed by fresh telemea made from cow milk. Antimicrobial susceptibility testing revealed higher resistance rates for oxacillin and trimethoprim-sulfamethoxazole (13.95% each), while all isolates were susceptible to ciprofloxacin, levofloxacin, and moxifloxacin. Conclusions: The findings emphasize the need for continuous monitoring of Listeria monocytogenes in dairy products, particularly ice cream and fresh cheeses, due to their high contamination rates. The study’s results are valuable for comparative analysis with findings from other countries, helping to establish a broader understanding of Listeria monocytogenes contamination trends and resistance profiles.